PSO based Grid Tied PV System with Three Phase Dual Buck Inverter - Prasad, N.; Hema Silviavinothini, S.; Muthuvel, K.; Parthiban, S. (International Journal of Psychosocial Rehabilitation, 2019)
Solar PV method provides a sustainable method for power production. The Solar panel has a nonlinear characteristic so that power extracting from solar panel becomes tedious especially when there is partial shading. Particle swarm optimization based Maximum Power Point Tracking is used, which tracks the maximum power from the Solar panel during partially shaded condition. Interleaved Boost converter which has minimum output voltage ripple is used. This paper proposes a method for grid interactive inverters for solar PV power generation. Three phase dual buck inverter which avoids shoot through problem is investigated. All simulations are done with MATLAB/ SIMULINK.